Pendugaan Pola Genetik dan Fenotipik Sifat Reproduksi Ternak Babi di Provinsi Bali (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
The aim of this study was to estimate genetic parameters on reproduction traits such as litter size, preweaning mortality and the number of piglet weaned. The data used were obtained from Artificial Insemination (AI) unit  Baturiti. Estimation of breeding values were calculated with heritability and differensial selection. Genetic and phenotypic trends analysis were performed with the regression mean breeding values on birth year and mean phenotypic on birth year. According to the breeding value estimated for all traits, the best was the sire no. 32, whose breeding value for litter size, mortality and number weaned were +0.27, +0.01, and +0.35.  The highest genetic and phenotypic  correlation were obtained between litter size and number of piglet weaned were 0.91 and 0.92 respectively. Genetic trends of litter size and number piglet weaned showed a similar pattern in 2010 to 2015 were fluctuative then declined in 2016, whereas the preweaning mortality tend to be stable. The phenotypic trends of litter size and the number of piglet weaned from 2010 through 2016 have the same pattern, which has a fluctuative pattern and lead to decrease in 2016. The phenotypic trend of pre-weaning mortality showed a stable pattern. The results of this research indicated that the reproduction traits of pig in Bali Province could be improve through selection programme.